2012
DOI: 10.1017/s0021932012000703
|View full text |Cite
|
Sign up to set email alerts
|

Birth Seasonality as a Response to a Changing Rural Environment (Kayes Region, Mali)

Abstract: Birth seasonality responds to a variety of environmental and socio-cultural factors. The present study was carried out to quantify the trends in seasonal variation in birth rate in seven districts in the Kayes region of Mali between 2007 and 2010 and to attempt to link climatic- and agricultural-cycle-dependent factors with birth seasonality. Lagged regression analysis based on time series analysis techniques was used to investigate seasonality of births registered in health facilities and its association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…Past research has examined the relationship between nutrition, agriculture, fecundity, and fertility levels, often from an anthropological and demographic perspective, and with a focus on questions of seasonality (e.g., Huss-Ashmore 1988; Bailey et al 1992; Ellison et al 1993; Dorélien 2016; Philibert 2013). The idea is that when childbearing women face seasonal food constraints, their reproductive outcomes change in response.…”
Section: Birth Seasonality Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has examined the relationship between nutrition, agriculture, fecundity, and fertility levels, often from an anthropological and demographic perspective, and with a focus on questions of seasonality (e.g., Huss-Ashmore 1988; Bailey et al 1992; Ellison et al 1993; Dorélien 2016; Philibert 2013). The idea is that when childbearing women face seasonal food constraints, their reproductive outcomes change in response.…”
Section: Birth Seasonality Frameworkmentioning
confidence: 99%
“…The idea is that when childbearing women face seasonal food constraints, their reproductive outcomes change in response. Bongaarts (1993) identifies six proximate determinants of birth seasonality that can be broadly categorized as either behavioral or biological (Panter-Brick 1996, Philibert et al 2013). Duration of postpartum infecundability, coital frequency, and age at marriage make up the behavioral components while the age at onset of sterility, intrauterine mortality, and conception failure are categorized as the biological components.…”
Section: Birth Seasonality Frameworkmentioning
confidence: 99%
“…An Indian study ( Yadava, 1979 ) reported their maximum indices of deliveries in the months of August to October and lowest from April to June. In Africa, a study from Mali ( Philibert et al, 2013 ) showed that rates of health-facility-attended deliveries were high in April-June, then fell rapidly and rose again in August-October.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is rainfall. Bronson (1995) argued that, especially in tropical subsistence societies, rain plays an important role in determining food availability and, thus, may influence birth seasonality through this channel (see also the more recent work carried out by Philibert et al 2013).…”
Section: The Three Main Explanations For Birth Seasonalitymentioning
confidence: 99%